P6_2 Mike Drop: Calculating the stretch of rope - Loch, Callum; Edkins, Troy; Nicholls, Tristram; Woodcock, Nathaniel (Physics Special Topics, 2022)
Young’s Modulus is used to calculate the stretch of a material based on the force exerted and the initial length. In this paper, this principal value will be used to calculate the predicted stretch of a sampled dynamic climbing rope due to falls of sequential heights and compare them to the advertised stretch specification.